Design of passivity‐based stabilized control of grid‐connected inverter system with LCL filter. Issue 2 (9th April 2019) - Kato, Toshiji; Inoue, Kaoru; Nakajima, Yusuke; Yamamoto, Yuki
Abstract: Instabilities due to mutual interactions between inverters and grid impedance are observed sometimes. This paper proposes a new stabilization method, which improves the output frequency impedance characteristics, satisfying the Nyquist stability criterion. The principle is that the output impedance is designed to be passive with the feedfoward loop characteristics and the system is stable even for an unknown grid system impedance. The design principle for the proposed stabilization method is described and investigated and validated on the basis of simulation and experimental results.